Islamic Ethics in Tension: Kafa’ah and Amanah in Indonesian Islamic Party Recruitment - Baderan, Suprisno; Fata, Ahmad Khoirul; Yasin, Hendra; Santoso, Eka Putra B.; Muhammad Hilmi (KALAM, 2026)
This article examines the tension between Islamic ethical ideals and political practice in leadership recruitment within Indonesian Islamic parties, with particular reference to al-kafa’ah (competence) and al-amanah (integrity). While Law No. 2 of 2011 mandates democratic and transparent recruitment, the institutionalization of these ethical principles remains contested. This study employs a normative juridical approach combined with qualitative analysis to investigate recruitment mechanisms in two major Islamic parties: the Prosperous Justice Party (PKS) and the United Development Party (PPP). The findings demonstrate that recruitment processes are predominantly shaped by political pragmatism, elite bargaining, and short-term electoral considerations, rather than by competence and integrity. This results in a persistent gap between normative commitments and institutional practice. The study identifies three structural constraints: elite-dominated decision-making, weak institutionalization of ethical standards, and the absence of independent ethical oversight. This article argues that the marginalization of al-kafa’ah and al-amanah reflects deeper structural tensions between Islamic ethical frameworks and the logic of modern electoral politics. By highlighting these tensions, the study contributes to broader debates on Islamic political ethics and institutional reform. Strengthening institutional design and embedding ethical principles within recruitment systems are essential for enhancing the credibility of Islamic parties and their role in democratic consolidation in Indonesia. [Artikel ini mengkaji ketegangan antara ideal etika Islam dan praktik politik dalam rekrutmen kepemimpinan partai Islam di Indonesia, dengan fokus pada prinsip al-kafa’ah (kompetensi) dan al-amanah (integritas). Meskipun Undang-Undang No. 2 Tahun 2011 mensyaratkan rekrutmen yang demokratis dan transparan, institusionalisasi prinsip-prinsip etika tersebut masih bersifat problematis. Penelitian ini menggunakan pendekatan yuridis normatif yang dikombinasikan dengan analisis kualitatif untuk mengkaji mekanisme seleksi kepemimpinan pada Partai Keadilan Sejahtera (PKS) dan Partai Persatuan Pembangunan (PPP). Hasil penelitian menunjukkan bahwa proses rekrutmen lebih banyak dipengaruhi oleh pragmatisme politik, negosiasi elite, dan pertimbangan elektoral jangka pendek, dibandingkan dengan prinsip kompetensi dan integritas. Kondisi ini menimbulkan kesenjangan yang persisten antara komitmen normatif dan praktik institusional. Penelitian ini mengidentifikasi tiga kendala struktural utama, yaitu dominasi pengambilan keputusan oleh elite, lemahnya institusionalisasi standar etika, serta ketiadaan mekanisme pengawasan etika yang independen. Artikel ini berargumen bahwa marginalisasi al-kafa’ah dan al-amanah mencerminkan ketegangan struktural antara kerangka etika Islam dan logika politik elektoral modern. Dengan menyoroti ketegangan tersebut, penelitian ini berkontribusi pada perdebatan yang lebih luas mengenai etika politik Islam dan reformasi kelembagaan. Penguatan desain institusional dan integrasi prinsip-prinsip etika dalam sistem rekrutmen menjadi langkah penting untuk meningkatkan kredibilitas partai Islam serta perannya dalam konsolidasi demokrasi di Indonesia.]